2013
DOI: 10.1016/j.aquatox.2013.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and metal-induced gene transcription of two new copper zinc superoxide dismutases in the solitary ascidian Ciona intestinalis

Abstract: a b s t r a c tAntioxidant enzymes are known to protect living organisms against the oxidative stress risk, also induced by metals. In the present study, we describe the purification and molecular characterization of two Cu,Zn superoxide dismutases (SODs), referred to as Ci-SODa and Ci-SODb, from Ciona intestinalis, a basal chordate widely distributed in temperate shallow seawater. The putative amino acid sequences were compared with Cu,Zn SODs from other metazoans and phylogenetic analyses indicate that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 61 publications
7
21
0
Order By: Relevance
“…Virtually all eukaryotic cells contain Cu,Zn SODs [37][38][39][40][41][42], as well as other anti-stress proteins that allow species to withstand environmental stresses of both natural and anthropogenic origin [43][44][45][46][47][48][49][50][51][52][53]. Our results indicated that a gene coding for cytosolic Cu,Zn SOD is present in the genome of the Antarctic icefish C. hamatus and is expressed as active protein in various organs.…”
Section: Discussionmentioning
confidence: 86%
“…Virtually all eukaryotic cells contain Cu,Zn SODs [37][38][39][40][41][42], as well as other anti-stress proteins that allow species to withstand environmental stresses of both natural and anthropogenic origin [43][44][45][46][47][48][49][50][51][52][53]. Our results indicated that a gene coding for cytosolic Cu,Zn SOD is present in the genome of the Antarctic icefish C. hamatus and is expressed as active protein in various organs.…”
Section: Discussionmentioning
confidence: 86%
“…not only at the gene transcriptional level but also at the posttranscriptional level (i.e., translation or post-translational modification) as indicated by Ferro and his co-authors [65]. Nrf2 is involved in the regulation of antioxidant enzyme gene transcription in fish [71].…”
Section: Deficiency Caused Oxidative Damage and Disturbed The Antimentioning
confidence: 97%
“…These results might represent a feedback mechanism that cause a decrease in the GSH content that requires an increase in GR for re-generation when the fish are subjected to MI deficiency. SOD is a free oxygen radical-scavenging enzyme that is responsible for the first line of defence against ROS [65]. Eukaryotes possess two major types of SOD: the cytoplasmic form CuZnSOD and the mitochondrial form MnSOD [66].…”
Section: Deficiency Caused Oxidative Damage and Disturbed The Antimentioning
confidence: 99%
“…Similar results were observed in our previous study with fish exposed to another dietary antinutrient factor β-conglycinin (24) . Second, it might be related to influences on enzyme activities that occurred not only at the gene transcriptional level but also at the post-transcriptional (such as translation, post-translational modification and so on) levels, just as Ferro et al (55) indicated. The GSTs represent an important group of enzymes that detoxify both endogenous compounds and foreign chemicals such as pharmaceuticals and environmental pollutants (56) .…”
Section: Glycinin-depressed Fish Growth Performance and Impaired Intementioning
confidence: 99%